2022
DOI: 10.2196/35065
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile App for Prevention of Cardiovascular Disease and Type 2 Diabetes Mellitus: Development and Usability Study

Abstract: Background Cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM) are posing a huge burden on health care systems worldwide. Mobile apps can deliver behavior change interventions for chronic disease prevention on a large scale, but current evidence for their effectiveness is limited. Objective This paper reported on the development and user testing of a mobile app that aims at increasing risk awareness and engaging users in behavior change. It… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 81 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Five of these required users to enter numerical values, while the remaining questions had answer options provided. During the usability study, app testers needed less than 5 minutes to complete the process [ 6 ]. Participants could update their risk at any time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five of these required users to enter numerical values, while the remaining questions had answer options provided. During the usability study, app testers needed less than 5 minutes to complete the process [ 6 ]. Participants could update their risk at any time.…”
Section: Methodsmentioning
confidence: 99%
“…It included links to external websites, educational videos, and the user guide. We published a detailed description of the app elsewhere [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BCTTv1 serves as a standardized language for describing distinct BCTs, which serve as the active ingredients in interventions; it lays the foundation for the reliable and systematic specification of behavior change interventions [15]. The appropriateness of an intervention and BCT can be assessed by applying the affordability, practicability, effectiveness/cost-effectiveness, acceptability, side effects/safety, and equity (APEASE) criteria, which acknowledge contextual factors that may influence implementation and have been previously used in the development of health apps to ensure app design simplicity and user-friendliness [25]. [24] which is published under the Creative Commons Attribution 4.0 International License (CC-BY) [26].…”
Section: The Bcw Approachmentioning
confidence: 99%
“…In recent years, there has been a steady increase in the number of apps addressing CVD risk factors such as diabetes mellitus (DM), hypertension (HTN), and lifestyle habits such as physical inactivity, smoking, unhealthy diet, and stress. 5 10 Even though randomized trials reported improvements in lifestyle and risk factor control, the effects of mHealth apps on disease prevention and outcomes remain controversial. 11 15 One of the reasons for the inconsistency in reported results might be the varying quality of mHealth apps.…”
Section: Introductionmentioning
confidence: 99%